Splenectomy modulates early immuno-inflammatory responses to trauma-hemorrhage and protects mice against secondary sepsis. Issue 1 (December 2018) - Drechsler, S.; Zipperle, J.; Rademann, P.; Jafarmadar, M.; Klotz, A.; Bahrami, S.; Osuchowski, M.
Abstract In polytrauma patients, the impact of splenectomy is equivocal, ranging from negative to protective. We investigated the impact of splenectomy on immune responses in the 1st -hit polytrauma alone and on survival in the post-traumatic sepsis (2nd hit). Female BALB/c mice underwent polytrauma (1st hit) consisting of either a) TH: femur fracture, hemorrhagic shock or b) TSH: splenectomy, femur fracture, hemorrhagic shock. Additionally, the polytrauma hit was followed by cecal ligation and puncture (CLP) 48 h later and compared to CLP alone. Splenectomy improved the 28-day survival in secondary sepsis to 92% (from 62%), while TH lowered it to 46% (p < 0.05). The improved survival was concurrent with lower release of inflammatory cytokines (IL-6, CXCL-1, MCP-1) and increase of C5a post-CLP. In the polytrauma hit alone, TSH induced stronger neutrophilia (1.9 fold) and lymphocytosis (1.7 fold) when compared to TH mice. Moreover, TSH resulted in a 41% rise of regulatory T-cells and reduced the median fluorescence intensity of MHC-2 on monocytes by 55% within 48 h (p < 0.05). Conversely, leukocyte phagocytic capacity was significantly increased by 4-fold after TSH despite a similar M1/M2 macrophage profile in both groups. Summarizing, splenectomy provoked both immuno-suppressive and immuno-stimulatory responses but was life-saving in secondary sepsis. Additionally, the polytrauma components in 2-hit models should be tested for their effects on outcome; the presumed end-effect of the 1st hit solely based on the common immuno-inflammatory parameters could be misleading.